Effect of GDP with respect to the Nominal and Real GDP of India: 2014-‘15 - Ayu Salmah, Ninin Non; Chauhan, Rahul; Maria Valianti, Reva; Maseleno, Andino (Opción, 2019)
Indian economy is likely to grow in the range of 5.4 to 5.9 per cent in 2014- 15 overcoming the sub-5 per cent GDP growth of past two years, even as poor monsoon and disturbed external environment remain a cause for concern, says the Economic Survey. Survey says that with the global economy expected to recover moderately, particularly on account of performance in some advanced economies, the economy can look forward to better growth prospects in 2014-15 and beyond. After recovering in 2009-10 and 2010-11, GDP growth slowed down to decade’s low of 4.5 per cent in 2012-13. It picked up marginally to 4.7 per cent in 2013-14. The survey further said the measures taken by the government to improve investment climate and improve governance could push up growth to 7-8 per cent in the coming years. The survey also made a case for repealing of archaic laws governing market access, expansion and entry/exit of firms and restore of the dispute resolution mechanism for com- mercial disputes to lend greater predictability to policy, giving boost to physical infrastructure and improving productivity in agriculture. The main aim of this paper is to analyse the effect of real and nominal GDP and to see the performance of GDP in past years and also to find out effect on economy by changing the real and nominal GDP and to see sectors wise GDP perfor- mance.